FAKTOR-FAKTOR YANG MEMENGARUHI INFLASI INTI DI INDONESIA - Ratna Christianingrum; Riza Aditya Syafri (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2019)
Inflation is an important macroeconomic indicator. High inflation can reduce real income, which mean there is a decrease of purchasing power. The level and volatility of Indonesia’s inflation have been higher compared with the trend in emerging market and developing country. This reseach is conducted to analyze the influence of fuel price, interest rate, GDP, gold price, IPI, exchange rate and money supply to core inflation rate in Indonesia. Data analysis was done by using Vector Error Correction Models (VECM). The result show that in short-run GDP, IPI, exchange rate, and money supply have significant effect to core inflation rate. In long-run, fuel price, GDP, and exchange rate have significant effect to core inflation rate in Indonesia.